Methane Production by Seagrass Ecosystems in the Red Sea - Garcias-Bonet, Neus; Duarte, Carlos M. (Frontiers in Marine Science, 2017)
Atmospheric methane (CH4) is the second strongest greenhouse gas and it is emitted to the atmosphere naturally by different sources. It is crucial to define the dimension of these natural emissions in order to forecast changes in atmospheric CH4 mixing ratio in future scenarios. However, CH4 emissions by seagrass ecosystems in shallow marine coastal systems have been neglected although their global extension. Here we quantify the CH4 production rates of seagrass ecosystems in the Red Sea. We measured changes in CH4 concentration and its isotopic signature by cavity ring-down spectroscopy on chambers containing sediment and plants. We detected CH4 production in all the seagrass stations with an average rate of 85.09 ± 27.80 µmol CH4 m-2 d-1. Our results show that there is no seasonal or daily pattern in the CH4 production rates by seagrass ecosystems in the Red Sea. Taking in account the range of global estimates for seagrass coverage and the average seagrass CH4 production, the global CH4 production and emission by seagrass ecosystems could range from 0.09 to 2.7 Tg yr-1. Because CH4 emission by seagrass ecosystems had not been included in previous global CH4 budgets, our estimate would increase the contribution of marine global emissions, hitherto estimated at 9.1 Tg yr-1, by about 30%. Thus, the potential contribution of seagrass ecosystems to marine CH4 emissions provides sufficient evidence of the relevance of these fluxes as to include seagrass ecosystems in future assessments of the global CH4 budgets.